THE EFFECT OF NURSE’S KNOWLEDGE ABOUT PATIENT SAFETY, WORKLOAD AND WORK MOTIVATION ON NURSE COMPLIANCE IN IMPLEMENTATION OF PATIENT FALL PREVENTION IN THE INFANT ROOM OF HOSPITAL X JAKARTA - Muliawan, Marjono; Nofierni, Nofierni; Dewi, Sandra (Journal of Hospital Management, 2022)
Knowledge is very closely related to behavior, the practice of documenting nursing care must be sustainable which pays attention to patient safety. Workload and motivation also play an important role in improving behavior, high motivation and low workload have a positive effect on the behavior of a nurse in a hospital in the application of patient fall prevention. The purpose of this study was to determine the effect of nurses' knowledge on patient safety, workload and work motivation on nurse compliance. Quantitative type with a cross sectional approach with a sample of 117 people which is the total population with a statistical test t-test. The results showed that the characteristics of nurses aged < 20-30 years (61.5%), female (95.7%), D3 Nursing education (70.9%), working years > 3 years (62.4%) and serving on the 3rd floor (47.0%). Nurses have high knowledge of 99.7, high workload with a score of 101.22, high motivation, a score of 95.70 and compliance with a score of 100.1. The bivariate test has a relationship between knowledge and compliance (p-value: 0.021), workload (p-value: 0.000) and there is no relationship between motivation and compliance (p-value: 0.961). And there is a relationship between knowledge and workload on motivation (p-value: 0.000). Multivarite test found that knowledge and workload with a significance of <0.05, but knowledge has the smallest significant (p-value = 0.000). It is recommended to the hospital to increase the knowledge of nurses about patient safety, namely by providing education and training regularly both internally and externally to all nurses who work in the inpatient room.